First record of the symbiotic palaemonid shrimp Pontonides sibogae Bruce, 2005 (Crustacea, Decapoda, Palaemonidae) from Korea - Jin-Ho Park; Sammy De Grave; Taeseo Park (Biodiversity Data Journal, 2022)
A single specimen of Pontonides sibogae was collected from a dendrophylliid coral by trimix SCUBA diving at a depth of 75 m during fieldwork around Jejudo Island, Korea in 2020. The morphology of the specimen corresponds closely to the main diagnostic characters of the holotype, especially in the presence of a distinct tubercle on the eyestalk, as well as the second pereiopod with fusiform setae along the dorsal border of the ischium.The genus Pontonides had previously not been reported from Korean waters. Herein, colour photographs are provided, as well as an illustrated description including previously unreported characteristics.